PENGARUH GOOD CORPORATE GOVERNANCE DAN FIRM SIZE PADA KINERJA PERUSAHAAN MANUFAKTUR DI INDONESIA - Gita Pramita, Anak Agung Sagung Mas (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p07, 2024)
This study aims to determine and obtain empirical evidence regarding the effect of good corporate governance and firm size on the performance of manufacturing companies in Indonesia. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The method of determining the sample used is purposive sampling. The number of companies that meet the criteria are 39 companies with 117 observations in 3 years. The data collection method used in this research is the documentation method. This study uses data analysis techniques in the form of multiple linear regression analysis. The results showed that managerial ownership and firm size had a significant negative effect on firm performance, while institutional ownership, independent commissioners and audit committees had no effect on firm performance.